At the heart of the classroom: student perspective on teaching methods in Cardiology - Tudela Aybar, Maria Judith; Larrubia-Valle, Jose I.; Pelaez Berdun, Cristian; Carmona-Segovia, Ada del Mar; Pavón-Morón, Francisco Javier; Jiménez-Navarro, Manuel F. (Spanish Journal of Medical Education, 2025)
Medical education has evolved towards a focus on competencies and practical skills. In response to changing demands, medical faculties have adopted methodologies that promote active and participative learning, enhancing student motivation and performance. Tools such as Miller’s Pyramid and Bloom’s Taxonomy guide planning and evaluation, integrating levels of knowledge with practical skills and clinical competence. The aim of this investigation was to study more deeply the student perspective on the teaching methods applied in the "Diseases of the Circulatory System" subject. To achieve that objective, a questionnaire was designed to assess the evaluation of teaching methods in Cardiovascular Medicine and to identify statistical differences between variables. This was distributed online to students from the University of Malaga and included sections on sociodemographic variables, perception of acquired competencies, preferred teaching methods, and new teaching assumptions. The study involved 121 students (32.2% male and 67.8% female), with a median grade point average of 7.8. The majority were in their sixth year (57%), followed by fifth year (24.8%) and fourth year (18.2%). Knowledge of cardiovascular risk factors was acquired by 99.2% of students, while cardiopulmonary auscultation was acquired by only 43.8%. The most valued teaching methods were clinical practices, seminars and workshops, and problem-based learning. Notably, lectures with a more dynamic approach were widely welcomed. In conclussion, integrated teaching in Cardiology enhances learning; students perceive the need to implement dynamic and practical methods that reflect real clinical scenarios.